Money Laundering: Risks and Socioeconomic Consequences in the Colombo-Venezuelan Border (London Journal of Research In Humanities and Social Sciences, 2024)
The following documentary review article analyzes the risks and socio-economic consequences of money laundering in the border area between Colombia and Venezuela (Norte de Santander – Táchira), through text mining and documentary exploration with the purpose of identifying the main negative effects that money laundering has on the country’s development and the adverse consequences that this activity has for the economic growth of the region. Specific factors are characterized regarding the underground economy and the unfavorable effects on the development of society, concluding that border areas are more affected by this criminal practice since smuggling has become a frequent means of money laundering and is more present than it would be in central areas of the country. This situation may occur due to the difficulty for the state to audit bilateral border operations and/or the imminent presence of underground economies in this area of the country.
Keywords: The Space The Existence Basic Energy Intellectual Energy The Time The Energy The Information Matter Cosmic origin; Teaching and Learning; translation; indigenous languages; language policy; African languages; Language of Learning and Teaching (LoLT); multilingualism; Didactics; Critical Didactics; Renewed Critical Didactics; Israel; Middle east.; Palestine.; Oil; gas; geopolitics; Underground economy; illegality; money laundering; border